Thermally conductive resin composition and thermally conductive sheet
The thermal conductive resin composition with silicone resin, fillers, and dimethyl polysiloxane addresses the thermal conductivity and reliability issues in high-temperature applications by enhancing dispersibility and adhesion, achieving up to 5.3 W/(m·K) thermal conductivity and maintaining flexibility.
Patent Information
- Application Number
- JP2023113504
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-11
- Publication Date
- 2025-01-24
AI Technical Summary
Conventional thermal interface materials, such as those using metal oxides, fail to provide sufficient thermal conductivity and are prone to degradation at high temperatures, leading to reduced reliability and increased manufacturing costs in applications like electric vehicles where heat management is critical.
A thermal conductive resin composition comprising an additional reaction-type silicone resin, a thermal conductive filler, alkoxysilane, and dimethyl polysiloxane with multiple hydroxyl groups, which enhances heat resistance and flexibility by improving dispersibility and adhesion, even with less expensive fillers like alumina and magnesium oxide.
The composition achieves high thermal conductivity (up to 5.3 W/(m·K) with improved heat resistance and flexibility, maintaining reliability under high temperatures, thus addressing the limitations of existing materials.
Smart Images

Figure 2025011407000001_ABST
Abstract
Description
[Technical field]
[0001] The present technology relates to a thermally conductive resin composition and a thermally conductive sheet. [Background technology]
[0002] In general, thermal interface materials are composite materials in which a thermally conductive filler is dispersed in a resin such as an epoxy resin or a silicone resin. Metal oxides are often used as thermally conductive fillers. However, sheet-shaped molded bodies made of composite materials using metal oxides have a thermal conductivity in the thickness direction of only about 1 to 3 W / (m·K). For this reason, sheet-shaped molded bodies having higher thermal conductivity are required, and for example, a method of highly filling a thermally conductive resin composition with a thermally conductive filler having higher thermal conductivity is considered. Examples of commonly used thermally conductive fillers include alumina, aluminum nitride, zinc oxide, magnesium oxide (magnesia), aluminum hydroxide, and boron nitride.
[0003] With growing awareness of global warming, the automotive industry is promoting the development of eco-friendly vehicles, such as hybrid vehicles, plug-in hybrid vehicles, and electric vehicles, with the aim of reducing greenhouse gas emissions. In order to further improve the fuel efficiency of these eco-friendly vehicles, the inverters installed in these vehicles are becoming more powerful and smaller. Accordingly, the ICs, reactors, and other components inside the inverter are also becoming smaller, and the amount of heat they generate is increasing.
[0004] For such heat-generating parts, there is a method of improving the cooling efficiency of the parts and protecting them by, for example, interposing a heat-conductive silicone composition such as a heat-conductive silicone grease composition, a heat-conductive silicone gel composition, or a heat-conductive silicone potting composition of about 1 to 3 W / (m·K) between the heat-generating part and the cooler (see, for example, Patent Document 1). However, in order to further increase the amount of heat generated, there is a demand for the development of a heat-conductive resin composition with a thermal conductivity of 5 W / (m·K) or more. At the same time, there is a demand for low manufacturing costs as well as high thermal conductivity.
[0005] In order to obtain a thermally conductive resin composition that can realize high thermal conductivity at low cost, for example, it is considered to use less aluminum nitride or aluminum powder, which has been used conventionally, as a thermally conductive filler, and to use a lot of cheaper metal oxides such as crushed alumina. However, since metal oxides such as crushed alumina have lower thermal conductivity than aluminum nitride or aluminum powder, it is considered necessary to increase the total amount of thermally conductive filler in the thermally conductive resin composition in order to realize high thermal conductivity by using a lot of metal oxides such as crushed alumina. In order to increase the amount of thermally conductive filler filled in the thermally conductive resin composition, alkoxysilanes may be used.
[0006] The thermally conductive resin composition usually contains alkoxysilanes and organic compounds containing ionic components, metal components, and elements such as N, P, and S, which are brought in by the thermally conductive filler. If the amount of the thermally conductive filler in the thermally conductive resin composition is up to about 65% by volume, it is considered that the effects of the above substances (alkoxysilanes and organic compounds containing ionic components, metal components, and elements such as N, P, and S) can be ignored.
[0007] However, alkoxysilanes are hydrolyzable, and the hydrolysis of alkoxysilanes, dehydration condensation following hydrolysis, and volatilization of unreacted components may accelerate the deterioration of the heat resistance reliability of the thermally conductive resin composition when used at high temperatures. In addition, for example, in a thermally conductive composition in which an addition polymerization type silicone resin is used as a binder component, the above-mentioned ionic components and metal components may be inhibitors of the platinum catalyst that catalyzes the polymerization reaction of the addition polymerization type silicone resin. At this time, the silicone resin that did not contribute to the polymerization may oxidize (age) at high temperatures. Furthermore, after the thermally conductive resin composition is cured, the silicone resin that did not contribute to the polymerization may undergo reactions such as depolymerization, which may lead to a decrease in heat resistance reliability. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] Patent Publication No. 2021-113290 [Patent Document 2] Patent No. 6610429 [Patent Document 3] Patent No. 6613462 [Patent Document 4] Patent Publication No. 2021-176945 Summary of the Invention [Problem to be solved by the invention]
[0009] The present technology has been proposed in view of the above-mentioned conventional circumstances, and provides a thermally conductive resin composition and a thermally conductive sheet having good heat resistance reliability. [Means for solving the problem]
[0010] The thermally conductive resin composition according to the present technology contains an addition reaction type silicone resin, a thermally conductive filler, an alkoxysilane, and a dimethylpolysiloxane having two or more hydroxyl groups at one end of the molecular chain.
[0011] The thermally conductive sheet according to the present technology comprises a cured product of a thermally conductive resin composition that contains an addition reaction type silicone resin, a thermally conductive filler, an alkoxysilane, and a dimethylpolysiloxane having two or more hydroxyl groups at one end of the molecular chain. Effect of the Invention
[0012] The present technology can provide a thermally conductive resin composition having good heat resistance reliability. [Brief description of the drawings]
[0013] [Figure 1] FIG. 1 is a cross-sectional view showing an example of a semiconductor device to which a thermally conductive sheet is applied. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] In this specification, the average particle diameter (D50) of the thermally conductive filler (hereinafter simply referred to as "average particle diameter") refers to the particle diameter at which the cumulative curve of particle diameter values from the small particle diameter side of the particle diameter distribution is 50%, assuming that the entire particle diameter distribution of the thermally conductive filler is 100%. Note that the particle size distribution (particle size distribution) in this specification is determined on a volume basis. For example, a method using a laser diffraction type particle size distribution measuring device can be used to measure the particle size distribution.
[0015] <Thermal conductive resin composition> The thermally conductive resin composition according to the present technology contains an addition reaction type silicone resin (hereinafter also referred to as "component a"), a thermally conductive filler (hereinafter also referred to as "component b"), an alkoxysilane (hereinafter also referred to as "component c"), and a dimethylpolysiloxane having two or more hydroxyl groups at one end of the molecular chain (hereinafter also referred to as "component d").
[0016] Here, the thermally conductive resin composition consisting of components a, b, and c has good kneadability and can have a low viscosity. However, the thermally conductive resin composition consisting of components a, b, and c does not have good heat resistance reliability. For example, when it is made into a thermally conductive sheet, it deteriorates when placed in an environment of 170°C for 1000 hours, and the hardness (e.g., Asker C hardness) of the thermally conductive sheet increases by about 3 to 4 times.
[0017] Therefore, the thermally conductive resin composition according to the present technology can improve the heat resistance reliability by further containing component d in addition to components a to c. By containing component d in addition to components a to c, the thermally conductive resin composition can have good kneadability and low viscosity even when an inexpensive thermally conductive filler (for example, an amorphous thermally conductive filler described later) is used. In addition, by containing component d, the thermally conductive resin composition can improve the thermal conductivity and flexibility when made into a thermally conductive sheet. Furthermore, by using components c and d in combination, the thermally conductive resin composition can improve the heat resistance reliability when made into a thermally conductive sheet, for example, the thermally conductive sheet is less likely to deteriorate even after being placed in an environment of 170°C for 1000 hours, and the hardness (for example, Asker C hardness) of the thermally conductive sheet can be suppressed from increasing. In this way, the thermally conductive resin composition according to the present technology can maintain good flexibility even in a high-temperature environment.
[0018] <Component a> The thermally conductive resin composition according to the present technology uses a silicone resin as a binder resin for component A because it has excellent moldability and weather resistance, and has good adhesion and conformability to electronic components. In particular, from the viewpoint of improving moldability, weather resistance, and adhesion, it is preferable to use a silicone resin composed of a liquid silicone gel base agent and a curing agent.
[0019] Examples of such silicone resins include addition reaction type silicone resins, heat vulcanization type millable silicone resins (millable rubber) that use peroxide for vulcanization, etc. In particular, when the thermally conductive resin composition is applied to a thermally conductive sheet that is sandwiched between a heat generating body and a heat dissipating member, for example, adhesion between the heat generating surface and the heat sink surface of an electronic component is required, so addition reaction type silicone resins (addition reaction type liquid silicone resins) are preferred.
[0020] Examples of the addition reaction type silicone resin include two-component addition reaction type silicone resins that are composed of (i) a silicone having an alkenyl group as the main component, (ii) a base agent containing a curing catalyst, and (iii) a curing agent having a hydrosilyl group (Si-H group).
[0021] (i) As the silicone having an alkenyl group, for example, polyorganosiloxane having a vinyl group can be used. (ii) The curing catalyst is a catalyst for promoting the addition reaction between the alkenyl group in the silicone having an alkenyl group (i) and the hydrosilyl group in the curing agent having a hydrosilyl group (iii). (ii) As the curing catalyst, a catalyst well known as a catalyst used in a hydrosilylation reaction can be mentioned, for example, a platinum group curing catalyst, for example, a platinum group metal such as platinum, rhodium, palladium, etc., or platinum chloride can be used. (iii) As the curing agent having a hydrosilyl group, for example, a polyorganosiloxane having a hydrosilyl group can be used. By adopting such a constitution, it is easy to highly fill component b, and the curing temperature can be easily adjusted by a catalyst or the like.
[0022] The addition reaction type silicone resin may be a commercially available product, taking into consideration the hardness of the cured product obtained by curing the thermally conductive resin composition. Examples of commercially available products of the addition reaction type silicone resin include CY52-276, CY52-272, EG-3100, EG-4000, EG-4100 (all manufactured by Dow-Toray), KE-1800T, KE-1031, KE-1051J (all manufactured by Shin-Etsu Chemical Co., Ltd.). The addition reaction type silicone resin may be used alone or in combination of two or more types.
[0023] <Component b> The thermally conductive resin composition according to the present technology contains a thermally conductive filler as component b. Component b is dispersed in component a. Component b can be selected from known substances in consideration of the desired thermal conductivity and filling property, and examples of the component b include metal hydroxides such as aluminum hydroxide and magnesium hydroxide, metals such as aluminum, copper, and silver, metal oxides such as alumina and magnesium oxide, metal nitrides such as aluminum nitride, boron nitride, and silicon nitride, carbon nanotubes, metal silicon, and fiber fillers (glass fibers, carbon fibers). Component b may be used alone or in combination of two or more types.
[0024] From the viewpoint of improving the thermal conductivity of the thermally conductive resin composition and reducing the production cost of the thermally conductive resin composition, it is preferable to use relatively inexpensive thermally conductive fillers (e.g., metal oxides such as alumina and magnesium oxide) in large quantities, without using relatively expensive thermally conductive fillers (e.g., aluminum nitride and aluminum) as much as possible. For example, as component b, it is preferable to use at least one of magnesium oxide and alumina, it is preferable to contain magnesium oxide, it is more preferable to use alumina and magnesium oxide in combination, and it is also possible to use only alumina and magnesium oxide.
[0025] From the viewpoint of improving the thermal conductivity of the thermally conductive resin composition, the thermally conductive resin composition preferably contains a spherical thermally conductive filler as component b. Here, the term "spherical" includes shapes such as almost spherical and elliptical in addition to a perfect sphere, and may have a sphericity of 0.8 or more, for example. The average particle size of spherical magnesium oxide, which is an example of a spherical thermally conductive filler, may be, for example, in the range of 0.1 to 150 μm, or may be in the range of 70 to 140 μm. The average particle size of spherical alumina, which is an example of a spherical thermally conductive filler, may be, for example, in the range of 0.1 to 50 μm, or may be in the range of 5 to 25 μm.
[0026] In addition, from the viewpoint of reducing the manufacturing cost of the thermally conductive resin composition, the thermally conductive resin composition preferably contains an amorphous thermally conductive filler in addition to the spherical thermally conductive filler as component b. That is, the thermally conductive resin composition preferably uses a spherical thermally conductive filler and an amorphous thermally conductive filler in combination as component b. The term "irregular shape" refers to a shape that does not correspond to a sphere and has an irregular shape and size, and includes shapes such as a flake shape, a needle shape, and a polyhedron. An amorphous thermally conductive filler is, for example, one that contains 70% or more by number of secondary particles in which at least a portion of the primary particles of a thermally conductive filler having a crystal phase and a grain boundary phase are fused to each other by the grain boundary phase, has an average particle size of 300 μm or less obtained by a laser diffraction scattering method, and has a ratio of the average particle size to the volume average circular equivalent diameter of the primary particles of the thermally conductive filler obtained by analysis of an image taken by a scanning electron microscope within the range of 2.8 to 5.0, because while being amorphous, it has fewer particles with a small particle size than particles obtained by crushing clumped raw materials or particles with a large particle size.
[0027] From the viewpoint of thermal conductivity, the amorphous thermally conductive filler is preferably, for example, amorphous magnesium oxide or amorphous alumina. The amorphous thermally conductive filler may have an average particle size in the range of 0.1 to 150 μm, 10 to 150 μm, 0.1 to 50 μm, or 60 to 130 μm. The amorphous thermally conductive filler has a BET specific surface area of 5 m or less. 2 / g or less, and 2 / g or less, and 0.1 to 5m 2 / g.
[0028] An embodiment of component b may be a combination of spherical alumina, amorphous alumina, and spherical magnesium oxide, or a combination of spherical alumina, amorphous alumina, and amorphous magnesium oxide having a crystal phase and a grain boundary phase.
[0029] As described above, in order to improve the thermal conductivity of the thermally conductive resin composition and reduce the manufacturing cost of the thermally conductive resin composition, it is preferable to use relatively inexpensive thermally conductive fillers (e.g., metal oxides such as alumina and magnesium oxide) as much as possible without using relatively expensive thermally conductive fillers (e.g., aluminum nitride and aluminum). However, since relatively inexpensive thermally conductive fillers have lower thermal conductivity than relatively expensive thermally conductive fillers, the total amount of thermally conductive fillers needs to be larger than when only relatively expensive thermally conductive fillers are used. Considering this viewpoint, the content of component b in the thermally conductive resin composition can be, for example, 70 to 95 mass% as the mass content in the thermally conductive resin composition, and may be 75 to 95 mass%, 80 to 95 mass%, 85 to 95 mass%, or 90 to 95 mass%. If the content of component b in the thermally conductive resin composition is less than 70 mass%, it tends to be difficult to obtain sufficient thermal conductivity. In addition, when the content of component b in the thermally conductive resin composition exceeds 95 mass%, it tends to be difficult to improve the kneadability. When two or more types of thermally conductive fillers are used in combination, it is preferable that the total amount thereof satisfies the above content range.
[0030] Since the irregular thermally conductive filler has a larger specific surface area than the spherical thermally conductive filler, if the irregular thermally conductive filler is used in large amounts, it tends to be difficult to improve the kneadability of the thermally conductive resin composition. Therefore, the content of the irregular thermally conductive filler relative to the total amount of component b in the thermally conductive resin composition is preferably 80 mass% or less.
[0031] <Ingredient c> The thermally conductive resin composition according to the present technology contains alkoxysilane (alkoxysilane compound) as component c. The alkoxysilane functions as a coupling agent (dispersant). The alkoxysilane becomes silanol through hydrolysis, and this silanol bonds with the surface of the thermally conductive filler, contributing to improving the dispersibility of the thermally conductive filler in the thermally conductive resin composition.
[0032] An alkoxysilane is a compound having a structure in which, for example, one to three of the four bonds that a silicon atom (Si) has are bonded to an alkoxy group, and the remaining bonds are bonded to an organic substituent.
[0033] Examples of the alkoxy group of the alkoxysilane include a methoxy group, an ethoxy group, a protoxy group, a butoxy group, a pentoxy group, and a hexatoxy group. The alkoxysilane may be contained as a dimer in the thermally conductive resin composition (or the thermally conductive sheet described later). From the viewpoint of availability, the alkoxysilane preferably has a methoxy group or an ethoxy group. From the viewpoint of further increasing the affinity with the thermally conductive filler, the number of alkoxy groups of the alkoxysilane is preferably three. A specific example of the alkoxysilane is preferably at least one selected from a trimethoxysilane compound and a triethoxysilane compound.
[0034] Examples of functional groups contained in the organic substituent of alkoxysilane include acryloyl group, alkyl group, carboxyl group, vinyl group, methacryl group, aromatic group, amino group, isocyanate group, isocyanurate group, epoxy group, hydroxyl group, and mercapto group. Here, when using, for example, an addition reaction type organopolysiloxane containing a platinum catalyst as the above-mentioned component a, it is preferable that the alkoxysilane is one that is unlikely to affect the curing reaction of the organopolysiloxane. Specifically, when using an addition reaction type organopolysiloxane containing a platinum catalyst, it is preferable that the organic substituent of the alkoxysilane does not contain an amino group, an isocyanate group, an isocyanurate group, a hydroxyl group, or a mercapto group.
[0035] From the viewpoint of further increasing the dispersibility of the thermally conductive filler and facilitating higher loading of the thermally conductive filler, the alkoxysilane is preferably an alkylalkoxysilane having an alkyl group bonded to a silicon atom, that is, an alkyl group-containing alkoxysilane. In the alkyl group-containing alkoxysilane, the number of carbon atoms of the alkyl group bonded to the silicon atom is preferably 4 or more, may be 6 or more, may be 8 or more, or may be 10 or more. In addition, from the viewpoint of further suppressing the viscosity of the thermally conductive resin composition, the number of carbon atoms of the alkyl group bonded to the silicon atom in the alkyl group-containing alkoxysilane is preferably 16 or less, may be 14 or less, or may be 12 or less. In the alkyl group-containing alkoxysilane, the alkyl group bonded to the silicon atom may be linear, branched, or cyclic.
[0036] A specific example of the alkoxysilane is a compound represented by the following formula A.
[0037] (Formula A) CH3(CH2) n Six3
[0038] In the formula A, n represents an integer of 5 to 15, and X represents a methoxy group or an ethoxy group. X in the formula A may be the same or different.
[0039] Specific examples of alkoxysilanes include, in addition to alkyl group-containing alkoxysilanes, vinyl group-containing alkoxysilanes, acryloyl group-containing alkoxysilanes, methacryl group-containing alkoxysilanes, aromatic group-containing alkoxysilanes, amino group-containing alkoxysilanes, isocyanate group-containing alkoxysilanes, isocyanurate group-containing alkoxysilanes, epoxy group-containing alkoxysilanes, mercapto group-containing alkoxysilanes, etc. Examples of alkyl group-containing alkoxysilanes include methyltrimethoxysilane, dimethyldimethoxysilane, trimethylmethoxysilane, methyltriethoxysilane, dimethyldiethoxysilane, ethyltrimethoxysilane, n-propyltrimethoxysilane, n-propyltriethoxysilane, isobutyltrimethoxysilane, isobutyltriethoxysilane, n-hexyltrimethoxysilane, n-hexyltriethoxysilane, cyclohexylmethyldimethoxysilane, n-octyltriethoxysilane, n-decyltrimethoxysilane, hexadecyltrimethoxysilane, etc. Among the alkyl group-containing alkoxysilanes, at least one selected from isobutyltrimethoxysilane, isobutyltriethoxysilane, n-hexyltrimethoxysilane, n-hexyltriethoxysilane, cyclohexylmethyldimethoxysilane, n-octyltriethoxysilane, n-decyltrimethoxysilane, and hexadecyltrimethoxysilane is preferred, and at least one of n-decyltrimethoxysilane and hexadecyltrimethoxysilane is more preferred. The alkoxysilanes may be used alone or in combination of two or more.
[0040] The content of component c in the thermally conductive resin composition can be, for example, in the range of 0.1 to 2.0 parts by mass, or may be in the range of 0.2 to 1.0 parts by mass, relative to 100 parts by mass of the thermally conductive filler. When two or more kinds of alkoxysilanes are used in combination, it is preferable that the total amount thereof satisfies the above content range.
[0041] <ingredient d> The thermally conductive resin composition according to the present technology contains, as component d, dimethylpolysiloxane having two or more hydroxyl groups at one end of the molecular chain. Component d also functions as a dispersant. By containing component d in addition to components a to c, the thermally conductive resin composition has good kneadability and low viscosity even when an inexpensive thermally conductive filler is used, as described above. In addition, by containing component d, the thermally conductive resin composition can have good flexibility and maintain heat resistance reliability, for example, good flexibility even in a high temperature environment. And, by containing component d, which also functions as a dispersant, the thermally conductive resin composition can be more highly filled with the thermally conductive filler, which is component b, and can have better thermal conductivity when made into a thermally conductive sheet.
[0042] Component d has two or more hydroxyl groups at one end of the molecular chain, and may have two or three hydroxyl groups. Component d is preferably a siloxane compound represented by the following formula 1.
[0043] (Formula 1) [ka] In equation 1, n 1 is an integer between 0 and 100, and R 1 is an alkyl group, and R 2 is an alkylene chain or an alkylene oxide chain, and R 3 ~R 5 are each independently an alkylene chain; R 6 is a hydrogen atom or an alkyl group.
[0044] In equation 1, n 1 may be an integer from 1 to 100.
[0045] In formula 1, R 1The number of carbon atoms in the alkyl group may be in the range of 1 to 12, 1 to 10, 1 to 8, 1 to 6, 1 to 5, or 1 to 4. The alkyl group may be a linear alkyl group or a branched alkyl group. 1 Specific examples include a methyl group, an ethyl group, a propyl group, and a butyl group.
[0046] In formula 1, R 2 When R is an alkylene chain, the number of carbon atoms in the alkylene chain may be in the range of 2 to 12, 2 to 10, 2 to 8, 2 to 6, 3 to 10, or 4 to 10. 2 When R is an alkylene oxide chain, the number of carbon atoms in the alkylene chain constituting the alkylene oxide chain may be in the range of 2 to 12, 2 to 10, 2 to 8, 2 to 6, 3 to 10, or 4 to 10. The alkylene chain may be linear or branched. 2 When R is an alkylene oxide chain, the number of oxygen atoms constituting the alkylene oxide chain may be 1, 2 or more, or may be in the range of 1 to 3. 2 Specific examples of the alkylene include an alkylene oxide chain consisting of an alkylene chain having 2 to 4 carbon atoms and an oxygen atom.
[0047] In formula 1, R 3 ~R 5 The number of carbon atoms in the alkylene chain may be in the range of 1 to 10, 1 to 8, 1 to 6, 1 to 4, or 1 to 3. The alkylene chain may be linear or branched. 3 ~R 5 A specific example of the alkyl group is a methylene chain.
[0048] In formula 1, R 6 When R is an alkyl group, the number of carbon atoms in the alkyl group may be in the range of 1 to 10, 1 to 8, 1 to 6, 1 to 4, or 1 to 2. The alkyl group may be linear or branched. 6 A specific example of an alkyl group is an ethyl group.
[0049] Furthermore, component d may be a siloxane compound represented by the following formula 2.
[0050] (Formula 2) [ka] In formula 2, n 2 is an integer equal to or greater than 1, and R 7 is an alkyl group.
[0051] In formula 2, n 2 may be an integer from 1 to 99.
[0052] In formula 2, R 7 The number of carbon atoms in the alkyl group may be in the range of 1 to 10, 1 to 8, 1 to 6, 1 to 5, or 1 to 4. The alkyl group may be a linear alkyl group or a branched alkyl group. R 7 Specific examples include a methyl group, an ethyl group, a propyl group, and a butyl group.
[0053] The number average molecular weight (Mn) of component d may be in the range of 1000 to 10000, 1000 to 7000, or 1000 to 5000. The number average molecular weight of component d refers to a value measured by gel permeation chromatography (GPC) (converted into standard polystyrene molecular weight).
[0054] Commercially available products of component d include FM-DA11, FM-DA21 (both manufactured by JNC Corporation), X-22-176DX (manufactured by Shin-Etsu Silicones), and X-22-176F (manufactured by Shin-Etsu Silicones).
[0055] In the thermally conductive resin composition, the content of component d may be 0.1 mass% or more, 0.2 mass% or more, 0.3 mass% or more, 0.4 mass% or more, or 0.5 mass% or more. In addition, in the thermally conductive resin composition, the content of component d may be 2 mass% or less, 1.5 mass% or less, 1.3 mass% or less, 1.2 mass% or less, or 1.1 mass% or less. In addition, in the thermally conductive resin composition, the content of component d may be in the range of 0.3 to 1.2 mass%. When two or more kinds of components d are used in combination, it is preferable that the total amount satisfies the above range.
[0056] The thermally conductive resin composition may further contain components other than the above-mentioned components a to d. For example, the thermally conductive resin composition may further contain a phenol-based antioxidant having an ester bond (hereinafter also referred to as "component e") as an antioxidant, or may use component e in combination with a sulfur-based antioxidant (hereinafter also referred to as "component f"). In addition, the thermally conductive resin composition may further contain additives such as reinforcing materials, colorants, heat resistance improvers, surfactants, dispersants, flame retardants, catalysts, curing retarders, deterioration inhibitors, and plasticizers, as necessary, for the purpose of further improving the performance of the thermally conductive resin composition or the thermally conductive sheet.
[0057] <ingredient e> From the viewpoint of obtaining a thermally conductive resin composition having superior heat resistance reliability, it is preferable to use a hindered phenol-based antioxidant as component e. A hindered phenol-based antioxidant has two sterically bulky groups (e.g., t-butyl groups) at two ortho positions of a phenolic hydroxyl group, which is an active site. Specific examples of phenol-based antioxidants include those having a structure represented by the following formula 3 as a hindered phenol skeleton. The hindered phenol-based antioxidant preferably has one or more skeletons represented by the following formula 3, and may have two or more skeletons represented by the following formula 3.
[0058] (Formula 3) [ka]
[0059] In formula 3, R 3 and R 4 represents a t-butyl group, and R 5 When represents a hydrogen atom (hindered type), R 3 represents a methyl group, and R 4 represents a t-butyl group, and R 5 When represents a hydrogen atom (semi-hindered type), R 3 represents a hydrogen atom, and R 4 represents a t-butyl group, and R 5 represents a methyl group (unhindered type). From the viewpoint of long-term thermal stability in a high-temperature environment, a semi-hindered type or a hindered type is preferred. The hindered phenol-based antioxidant preferably has three or more skeletons represented by formula 3 in one molecule, and the three or more skeletons represented by formula 3 are linked by a hydrocarbon group or a group consisting of a combination of a hydrocarbon group, -O-, and -CO-. The hydrocarbon group may be linear, branched, or cyclic. The carbon number of the hydrocarbon group may be, for example, 3 to 8. The molecular weight of the hindered phenol-based antioxidant may be, for example, 300 to 850, or may be 500 to 800.
[0060] In the present technology, it is preferable to use a hindered phenol-based antioxidant having an ester bond in its structure, i.e., a hindered phenol-based antioxidant having an ester bond. When an addition reaction type silicone resin is used as component a, the use of a hindered phenol-based antioxidant having an ester bond can more effectively prevent the oxidation of the addition reaction type silicone resin, and it is easy to obtain a thermally conductive resin composition having better heat resistance reliability. Examples of the hindered phenol antioxidant having such an ester bond include stearyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, pentaerythritol tetrakis[3-(3',5'-di-t-butyl-4'-hydroxyphenyl)propionate], 2,2'-dimethyl-2,2'-(2,4,8,10-tetraoxaspiro[5.5]undecane-3,9-diyl)dipropane-1,1'-diyl=bis[3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propanoate], and 3,9-bis[1,1-dimethyl-2-[β-(3-t-butyl-4-hydroxy-5-methylphenyl)propionyloxy]ethyl]2,4,8,10-tetraoxaspiro[5,5]-undecane.
[0061] Commercially available hindered phenol antioxidants having an ester bond include ADK STAB AO-50 (stearyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate), ADK STAB AO-60 (pentaerythritol tetrakis[3-(3',5'-di-t-butyl-4'-hydroxyphenyl)propionate]), ADK STAB AO-80 (3,9-bis[1,1-dimethyl-2-[β-(3-t-butyl-4-hydroxy-5-methylphenyl)propionyloxy]ethyl]2,4,8,10-tetraoxaspiro[5,5]-undecane) (all manufactured by ADEKA Corporation), Irganox 245, Irganox 1010 (tetrakis[3-(3',5'-di-t-butyl-4'-hydroxyphenyl)propionate]), and ADK STAB AO-120 (pentaerythritol tetrakis[3-(3',5'-di-t-butyl-4'-hydroxyphenyl)propionate]). pentaerythritol]propionate), Irganox1035 (2,2-thio[diethyl bis-3(3,5-di-t-butyl-4-hydroxyphenyl)propionate]), Irganox1076 (stearyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate), Irganox1135 (octyl 3-(4-hydroxy-3,5-diisopropylphenyl)propionate) (all manufactured by BASF), Sumilizer GA-80 (2,2'-dimethyl-2,2'-(2,4,8,10-tetraoxaspiro[5.5]undecane-3,9-diyl)dipropane-1,1'-diyl bis[3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propanoate]) (manufactured by Sumitomo Chemical Co., Ltd.), and the like. The component e may be used alone or in combination of two or more kinds.
[0062] When the thermally conductive resin composition contains component e, the content of component e in the thermally conductive resin composition may be, for example, 0.1 parts by mass or more, 0.5 parts by mass or more, 1 part by mass or more, or 2 parts by mass or more, when the content of component a in the thermally conductive resin composition is 100 parts by mass. In addition, the content of component e in the thermally conductive resin composition may be, for example, 10 parts by mass or less, 5 parts by mass or less, 3 parts by mass or less, or 2 parts by mass or less, when the content of component a in the thermally conductive resin composition is 100 parts by mass. When two or more kinds of component e are used in combination, it is preferable that the total amount thereof satisfies the above content range.
[0063] <Component f> From the viewpoint of obtaining a thermally conductive resin composition having superior heat resistance reliability, a sulfur-based antioxidant having a thioether skeleton or a hindered phenol skeleton can be used as component f. Examples of component f include ditridecyl 3,3'-thiobispropionate, pentaerythritol tetrakis[3-(dodecylthio)propionate], and 4,6-bis(octylthiomethyl)-o-cresol.
[0064] Commercially available products of component f include ADK STAB AO-412S, ADK STAB AO-503 (ditridecyl 3,3'-thiobispropionate), ADK STAB AO-26 (all manufactured by ADEKA CORPORATION), Sumilizer TP-D (manufactured by Sumitomo Chemical Co., Ltd.), and Irganox1520L (4,6-bis(octylthiomethyl)-o-cresol) (manufactured by BASF Japan Ltd.). Among these, tetrakis[3-(dodecylthio)propionate]pentaerythritol (commercially available products: ADK STAB AO-412S, SUMILIZER (registered trademark) TP-D) is preferred because it causes less curing inhibition. Component f may be used alone or in combination of two or more kinds.
[0065] When the thermally conductive resin composition contains component f, it is preferable to use it in combination with component e, and it is preferable to make the content of component f in the thermally conductive resin composition about the same amount as component e or more than component e. For example, the content of component f in the thermally conductive resin composition can be 0.1 parts by mass or more, 0.5 parts by mass or more, or 1 part by mass or more, when the content of component a in the thermally conductive resin composition is 100 parts by mass. In addition, the content of component f in the thermally conductive resin composition can be 20 parts by mass or less, 10 parts by mass or less, or 5 parts by mass or less, when the content of component a in the thermally conductive resin composition is 100 parts by mass. When two or more kinds of component f are used in combination, it is preferable that the total amount thereof satisfies the above content range.
[0066] As described above, the thermally conductive resin composition according to the present disclosure has good kneadability. The kneadability of the thermally conductive resin composition can be evaluated by the method described in the examples below.
[0067] The thermally conductive resin composition according to the present technology has good hardness. In other words, the thermally conductive resin composition according to the present technology can have a low viscosity. Therefore, the thermally conductive resin composition according to the present technology can be applied, for example, by a general coater. The hardness of the thermally conductive resin composition, when evaluated by the method described in the examples below, can be 22N or less, 21N or less, 20N or less, 17N or less, 15N or less, 15N or less, or in the range of 15 to 21N.
[0068] <Thermal conductive sheet> The thermally conductive sheet according to the present technology includes a cured product of the thermally conductive resin composition described above. The thermally conductive sheet according to the present technology may be made of a cured product of the thermally conductive resin composition described above. From the viewpoint of high thermal conductivity, the thermally conductive sheet according to the present technology has a higher thermal conductivity, and for example, the thermal conductivity in the thickness direction (initial thermal conductivity) can be 4.0 W / (m·K) or more, 4.9 W / (m·K) or more, 5.0 W / (m·K) or more, 5.1 W / (m·K) or more, 5.2 W / (m·K) or more, 5.3 W / (m·K) or more, in the range of 4.9 to 6.0 W / (m·K), in the range of 5.0 to 6.0 W / (m·K), or in the range of 5.0 to 5.3 W / (m·K). The thermal conductivity of the thermally conductive sheet can be measured by the method described in the examples described below.
[0069] The thermally conductive sheet according to the present technology can have good flexibility because it uses the above-mentioned thermally conductive resin composition. For example, the thermally conductive sheet according to the present technology can have an Asker C hardness of 25 or less, 21 or less, 20 or less, 19 or less, or in the range of 8 to 24. The Asker C hardness of the thermally conductive sheet can be measured by the method described in the examples below.
[0070] The thermally conductive sheet according to the present technology has good heat resistance reliability, and for example, the Asker C hardness after being placed in an environment of 170°C for 1000 hours can be 70 or less, can be 59 or less, can be 56 or less, can be 49 or less, or can be in the range of 30 to 59. The Asker C hardness of the thermally conductive sheet can be measured by the method described in the examples below.
[0071] The thermally conductive sheet according to the present technology can be obtained by applying a thermally conductive resin composition to a desired thickness on a release film formed from, for example, PET (polyethylene terephthalate), PEN (polyethylene naphthalate), polyolefin, polymethylpentene, glassine paper, etc., and then heating to cure component a. The thickness of the thermally conductive sheet can be appropriately selected depending on the purpose, and can be, for example, in the range of 0.05 to 5 mm.
[0072] <Electronic equipment> The thermally conductive sheet according to the present technology can be arranged between a heat generating body and a heat sink to form an electronic device (thermal device) having a structure in which the sheet is arranged between the heat generating body and the heat sink to dissipate heat generated by the heat generating body to the heat sink. The electronic device has at least the heat generating body, the heat sink, and the thermally conductive sheet, and may further have other members as necessary.
[0073] The heating element is not particularly limited, and examples thereof include integrated circuit elements such as CPUs, GPUs (Graphics Processing Units), DRAMs (Dynamic Random Access Memory), and flash memories, as well as electronic components that generate heat in electric circuits, such as transistors and resistors. Heating elements also include components that receive optical signals, such as optical transceivers in communication devices. Heating elements also include power devices, etc., described above as applications of the thermally conductive resin composition.
[0074] The heat dissipator is not particularly limited, and examples thereof include heat sinks and heat spreaders that are used in combination with integrated circuit elements, transistors, optical transceiver housings, etc. Examples of materials for heat sinks and heat spreaders include copper and aluminum. In addition to heat spreaders and heat sinks, the heat dissipator may be anything that conducts heat generated from a heat source and dissipates it to the outside, and examples of the heat dissipator include radiators, coolers, die pads, printed circuit boards, cooling fans, Peltier elements, heat pipes, vapor chambers, metal covers, housings, etc. The heat pipe is, for example, a hollow structure that is cylindrical, approximately cylindrical, or flattened.
[0075] FIG. 1 is a cross-sectional view showing an example of a semiconductor device to which a thermally conductive sheet is applied. For example, as shown in FIG. 1, the thermally conductive sheet 1 is mounted on a semiconductor device 50 built into various electronic devices and sandwiched between a heat generating body and a heat dissipating body. The semiconductor device 50 shown in FIG. 1 includes an electronic component 51, a heat spreader 52, and a thermally conductive sheet 1, and the thermally conductive sheet 1 is sandwiched between the heat spreader 52 and the electronic component 51. The thermally conductive sheet 1 is sandwiched between the heat spreader 52 and the heat sink 53, and together with the heat spreader 52, constitutes a heat dissipation member that dissipates heat from the electronic component 51. The mounting location of the thermally conductive sheet 1 is not limited to between the heat spreader 52 and the electronic component 51, or between the heat spreader 52 and the heat sink 53, and can be appropriately selected according to the configuration of the electronic device or semiconductor device. The heat spreader 52 is formed, for example, in a rectangular plate shape, and has a main surface 52a facing the electronic component 51 and a side wall 52b standing along the outer periphery of the main surface 52a. The heat spreader 52 has a thermally conductive sheet 1 provided on the main surface 52a surrounded by the side wall 52b, and a heat sink 53 provided, with the thermally conductive sheet 1 interposed between the main surface 52a and the other surface 52c opposite the main surface 52a. EXAMPLES
[0076] Hereinafter, examples of the present technology will be described. Note that the present technology is not limited to these examples.
[0077] <Preparation of Thermally Conductive Resin Composition> The raw materials used in preparing the thermally conductive resin composition are as follows.
[0078] <Addition reaction type silicone resin> An addition reaction type silicone resin comprising a mixture of an organopolysiloxane having an alkenyl group, a platinum catalyst, and an organopolysiloxane having a hydrosilyl group.
[0079] <Thermal conductive filler> Spherical alumina (average particle size 5~25μm) Irregular alumina (average particle size 0.1~50μm) Spherical magnesia (average particle size 70~140μm) Irregular magnesia with crystalline and grain boundary phases (average particle size 60-130μm)
[0080] <Alkoxysilane> Z-6210: n-Decylalkoxysilane (Dow Toray), boiling point 115°C Dynasylan 9116: Hexadecylalkoxysilane (manufactured by Evonik Japan)
[0081] <Dimethylpolysiloxane with two or more hydroxyl groups at one end of the molecular chain> FM-DA11: one-terminated diol (manufactured by JNC Corporation), number average molecular weight (Mn) 1000 (compound represented by the following formula 4) FM-DA21: one-terminated diol (manufactured by JNC Corporation), number average molecular weight (Mn) 2000 (compound represented by the following formula 4) X-22-176DX: one-terminated diol (manufactured by Shin-Etsu Silicones, a compound represented by the following formula 4)
[0082] (Formula 4) [ka]
[0083] <Antioxidants> AO-80: Hindered phenol antioxidant (ADEKA) AO-412S: Thioether antioxidant (ADEKA)
[0084] <Other ingredients> FM-0421: Single-terminal carbinol (JNC) KP-578: Graft copolymer of acrylic polymer and dimethylpolysiloxane (Shin-Etsu Silicone Co., Ltd.) KC-6003: Carbinol at both ends (Shin-Etsu Chemical Co., Ltd.) FM-9915: Both ends silanol (JNC) ZS-90: Heavy metal deactivator (ADEKA)
[0085] <Preparation of Thermally Conductive Resin Composition> A thermally conductive resin composition consisting of each component shown in Table 1 was prepared. A rotating and revolving stirrer was used for stirring, and the rotation speed was 1200 rpm. In Table 1, the amount of each component listed in the column of Examples or Comparative Examples is expressed in parts by mass unless otherwise specified. In Table 1, the column "Parts by mass (a)" represents the total mass of each component constituting the thermally conductive resin composition. In addition, in Table 1, the column "Filler content (parts by mass) (b)" represents the total mass of the thermally conductive filler in the thermally conductive resin composition. In addition, in Table 1, the column "Filler mass% (c) = (b) / (a)" represents the ratio (mass%) of the thermally conductive filler in the thermally conductive resin composition. In addition, in Table 1, "Irregular filler content (parts by mass) (d)" represents the total mass of the thermally conductive filler that is irregular in the thermally conductive resin composition. In addition, in Table 1, the column "% by mass of irregular filler in filler (e) = (d) / (b)" indicates the ratio (% by mass) of the total mass of the irregular thermally conductive filler to the total mass of the thermally conductive filler in the thermally conductive resin composition.
[0086] <Preparation of thermally conductive sheet> The thermally conductive resin composition was sandwiched between a 100 μm-thick PET base film that had been subjected to a release treatment and a 30 μm-thick PET cover film that had been subjected to a release treatment, and passed through a bar coater so that the thickness was 2 mm to obtain a precursor of the thermally conductive sheet. This precursor was cured by heating at 80° C. for 6 hours to obtain a thermally conductive sheet.
[0087] <Mixability> The kneadability of the thermally conductive resin composition was judged by visual inspection. Specifically, it was judged by visual inspection whether the kneaded composition had a gloss, no bubbles, and no particle aggregation. When the kneadability of the thermally conductive resin composition was good, that is, when the kneaded composition had a gloss, no bubbles, and no particle aggregation, it was evaluated as OK, and when it was otherwise, it was evaluated as NG. The results are shown in Table 1.
[0088] <Hardness> Using a tabletop physical property measuring instrument (manufactured by Yamaden, model number: TPU-2D), in texture measurement mode, the maximum load value (N) of the thermally conductive resin composition was evaluated as the hardness of the thermally conductive resin composition under the conditions of a plunger (cylindrical, diameter 16 mm, height 25 mm, contact area diameter 16 mm, sample height 13 mm), clearance setting: 2.0 mm, and measurement speed 5 mm / sec. The results are shown in Table 1. From the viewpoint of coatability, the hardness of the thermally conductive resin composition is preferably 22 N or less.
[0089] <Initial thermal conductivity> Using a thermal resistance measuring device conforming to ASTM-D5470, a load of 1kgf / cm 2 A voltage was applied to measure the initial thermal conductivity (W / (m K)) in the thickness direction of the thermally conductive sheet. The sheet temperature during measurement was 25°C. The results are shown in Table 1. For practical purposes, it is preferable that the initial thermal conductivity of a thermally conductive sheet is 4.0 W / (m K) or more.
[0090] <Flexibility (Asker C hardness)> As an indication of the flexibility of the thermally conductive sheet, the Asker C hardness of the thermally conductive sheet was measured in accordance with the standard JIS K7312. Specifically, the Asker C hardness was measured at a temperature of 25°C using a durometer (manufactured by Kobunshi Keiki Co., Ltd.; product name "Asker Rubber Hardness Meter Type C"). The results are shown in Table 1. From the viewpoints of adhesion and workability, the Asker C hardness of the thermally conductive sheet is preferably 25 or less.
[0091] <Heat resistance reliability (Asker C hardness)> As the heat resistance reliability of the thermal conductive sheet, the Asker C hardness of the thermal conductive sheet after the ultra heat resistance test at 170 ° C for 1000 hours was measured. That is, the Asker C hardness of the thermal conductive sheet after 1000 hours in an environment at 170 ° C was measured according to the standard of JIS K7312. Specifically, under the condition of a temperature of 25 ° C, the thermal conductive sheet after 1000 hours in an environment at 170 ° C was left at 25 ° C for 1 hour, and then the Asker C hardness was measured using a durometer (manufactured by Kobunshi Keiki Co., Ltd.; product name "Asker rubber hardness meter C type"). The results are shown in Table 1. From the viewpoint of maintaining thermal conductivity and flexibility, the Asker C hardness of the thermal conductive sheet after 1000 hours in an environment at 170 ° C is preferably 70 or less, more preferably 59 or less.
[0092] [Table 1]
[0093] In Examples 1 to 8, it was found that the heat resistance reliability was good by using a thermally conductive resin composition containing an addition reaction type silicone resin, a thermally conductive filler, an alkoxysilane, and a dimethylpolysiloxane having two or more hydroxyl groups at one end of the molecular chain. Specifically, it was found that the thermally conductive sheets using the thermally conductive resin compositions of Examples 1 to 8 had good flexibility even when placed under high temperatures.
[0094] It was also found that the thermally conductive sheets using the thermally conductive resin compositions of Examples 1 to 8 had good initial thermal conductivity. It was also found that the thermally conductive resin compositions of Examples 1 to 8 had good hardness. And it was also found that the thermally conductive resin compositions of Examples 1 to 8 had good kneadability.
[0095] In Comparative Examples 1 to 4 and 6, it was found that it was difficult to improve the heat resistance reliability because the thermal conductive resin composition used contained an addition reaction type silicone resin and an alkoxysilane, and did not contain dimethylpolysiloxane having two or more hydroxyl groups at one end of the molecular chain. Specifically, it was found that the thermal conductive sheets using the thermal conductive resin compositions of Comparative Examples 1 to 4 and 6 did not have good flexibility when placed under high temperatures.
[0096] It was also found that the thermal conductive resin composition of Comparative Example 1 was difficult to improve the heat resistance reliability and also had poor hardness. It was also found that the thermal conductive sheet using the thermal conductive resin composition of Comparative Example 1 did not have good flexibility even before being placed under high temperature.
[0097] Moreover, it was found that in Comparative Example 2, the hardness of the thermally conductive resin composition was also not good.
[0098] In addition, it was found that the kneadability of the thermally conductive resin composition was not good in Comparative Example 3, and it was difficult to prepare a thermally conductive sheet. Therefore, in Comparative Example 3, evaluation of anything other than the kneadability of the thermally conductive resin composition could not be performed.
[0099] Moreover, it was found that in Comparative Example 4, the thermally conductive sheet did not have good flexibility even before it was placed under high temperatures.
[0100] It was also found that the hardness of the thermally conductive resin composition was not good in Comparative Example 6. It was also found that the flexibility of the thermally conductive sheet before it was placed under high temperature was not good in Comparative Example 6.
[0101] In Comparative Example 5, a thermally conductive resin composition was used that contained an addition reaction type silicone resin, a thermally conductive filler, and dimethylpolysiloxane having two or more hydroxyl groups at one end of the molecular chain, and did not contain alkoxysilane, and it was found that it was difficult to improve the heat resistance reliability. Specifically, it was found that the thermally conductive sheet using the thermally conductive resin composition of Comparative Example 5 did not have good flexibility when placed under high temperatures. In addition, in Comparative Example 5, it was found that the flexibility of the thermally conductive sheet before being placed under high temperatures was also not good. Furthermore, in Comparative Example 5, it was found that the initial thermal conductivity of the thermally conductive sheet was also not good. [Explanation of symbols]
[0102] 1. Thermally conductive sheet, 50 Semiconductor device, 51 Electronic components, 52 heat spreader, 52a main surface, 52b side wall, 52c On the other side, 53 Heat sink
Claims
1. An addition reaction type silicone resin; A thermally conductive filler; Alkoxysilane, and a dimethylpolysiloxane having two or more hydroxyl groups at one end of the molecular chain.
2. The thermally conductive resin composition according to claim 1 , wherein the dimethylpolysiloxane is a siloxane compound represented by the following formula 1: (Formula 1) 【Chemistry 1】 In formula 1, n 1 is an integer from 0 to 100, R 1 is an alkyl group, R 2 is an alkylene chain or an alkylene oxide chain, R 3 ~R 5 are each independently an alkylene chain; R 6 is a hydrogen atom or an alkyl group.
3. The thermally conductive resin composition according to claim 1 , wherein the dimethylpolysiloxane is a siloxane compound represented by the following formula 2: (Formula 2) 【Chemistry 2】 In formula 2, n 2 is an integer of 1 or more, R 7 is an alkyl group.
4. The thermally conductive resin composition according to claim 1 or 2, wherein the thermally conductive filler contains an amorphous thermally conductive filler.
5. The thermally conductive resin composition according to claim 4 , wherein the thermally conductive filler contains magnesium oxide.
6. The thermally conductive resin composition according to claim 1 or 2, further comprising a phenolic antioxidant having an ester bond.
7. The thermally conductive resin composition according to claim 1 or 2, further comprising a sulfur-based antioxidant.
8. A thermally conductive sheet comprising a cured product of the thermally conductive resin composition according to claim 1 or 2.
9. The thermally conductive sheet according to claim 8, having a thermal conductivity of 4.0 W / (m·K) or more.
10. The thermally conductive sheet according to claim 8, having an Asker C hardness of 8 to 24.
11. The thermally conductive sheet according to claim 8, having an Asker C hardness of 30 to 59 after being placed in an environment of 170°C for 1000 hours.
Citation Information
Patent Citations
Heat-conductive silicone potting composition, and cured product of the same
JP2021113290A
Thermally conductive silicone composition and cured product thereof
JP2021176945A
Thermally conductive silicone composition, cured product thereof, and method for producing the same
JP6610429B2
Thermally conductive sheet
JP6613462B2